Pengaruh Current Ratio, Debt to Asset Ratio, dan Total Asset Turnover Terhadap Return On Assets pada Perusahaan Subsektor Rokok yang Terdaftar di Bursa Efek Indonesia - Sri Fatimah; M. Rimawan; Hanifah Muthiah (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of Current Ratio (CR), Debt to Asset Ratio (DAR), and Total Asset Turnover (TATO) on Return on Assets (ROA) in cigarette subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The population of this study includes all cigarette subsector companies listed on the IDX during the research period. The sampling technique used was purposive sampling, resulting in 4 companies as samples. The data analysis method applied is multiple linear regression analysis. The results show that Total Asset Turnover have a positive effect on ROA, while Current Ratio and Debt to Asset Ratio has a significant negative effect on ROA. These findings indicate that liquidity level, asset utilization efficiency, and capital structure influence the profitability level of the companies.